Proses Collaborative Governance pada Pariwisata Banyu Biru, Kabupaten Nganjuk - Muzaqi, Ajie Hanif; Tyasotyaningrum, Berlian; Wardhani, Tian Tri (Pusat Pembelajaran dan Strategi Kebijakan Talenta Aparatur Sipil Negara Nasional, 2024)
This study seeks to achieve two main objectives: first, analyzing the collaborative governance model as a strategy to develop “Banyu Biru” tourism in Gondongwetan Village, Nganjuk Regency, and second, knowing the opportunities and challenges of “Banyu Biru” tourism to be able to develop and compete with other tourism. This research is important to be carried out with the first consideration, Nganjuk Regency is weak in developing its tourism potential considering that its potential is sufficient to compete with other districts in East Java. Second, the local government still lacks collaboration in community empowerment, so it seems that the policy is not participatory. The research method we use is qualitative with a case study approach. The results of our analysis show that the starting conditions model has not run optimally due to the closed attitude of the community and local government to collaborate to empower Banyu Biru tourism, making it difficult to develop and accept new concept innovations. However, the natural and cultural tourism owned by Gondang Wetan Village has the potential to make it a tourist attraction, especially Banyu Biru plus the potential of MSMEs owned.